Gastroschisis: diagnosis, prognosis and treatment options - Rustemov, Dastan; Sakuov, Zhenis; Kucherbayeva, Zhuldyz; Shayakhmetov, Sherkhan; Bilal, Ruslan (Frontiers in Pediatrics, 2025)
Gastroschisis is a rare congenital anomaly characterized by extrusion of abdominal organs through a defect in the anterior abdominal wall, typically to the right of the umbilical cord. Despite advances in prenatal diagnostics and neonatal surgical care, gastroschisis remains associated with significant morbidity and mortality. This review summarizes recent epidemiological data, etiological hypotheses, diagnostic approaches, treatment strategies, and postoperative complications. Both simple and complicated forms are discussed, with emphasis on the impact of viscero-abdominal disproportion and associated anomalies. Recent modifications in surgical tactics, including staged reduction and innovative siloplasty techniques, are evaluated. The review highlights ongoing challenges in optimizing surgical timing, minimizing complications such as adhesive disease and necrotizing enterocolitis, and improving long-term outcomes.